The Need for a Paradigm Shift in Approaching Ageing-Related Design Research and Practice - Comincioli, Elena; Chirico, Alice; Gaggioli, Andrea; Masoodian, Masood (Frontiers in Psychology, 2021)
Despite a rapidly ageing world population, ageism – particularly in its implicit form – is widespread in society. In this article, we propose that a paradigm shift is needed in how we approach ageing-related design research and practice in areas such as assistive technologies. We also put forward the idea of using the Healthy Ageing (HA) framework of the WHO as the basis for new lines actions that can be taken by design researchers and practitioners to address implicit ageism in society through their work.